TEKNIK RIAS PENGANTIN DENGAN COMPLEXION TAHAN LAMA: STUDI KASUS OLEH MUA RASILIABRUSHES SERANG - Nanda Sabrina; Dwi Juliyanti Lestari; Hadiyatno Hadiyatno (Boting Langi: Jurnal Seni Pertunjukan, 2025)
This research aims to reveal the long-lasting complexion technique in bridal makeup applied by MUA Rasiliabrushes in Serang, Banten. The research uses a qualitative approach with a case study method, which allows researchers to deeply explore bridal makeup strategies from the aspect of practice and direct experience of the actors. Primary data was collected through interviews with MUAs, clients, photographers, and direct observation of the makeup process, while secondary data was obtained from literature and academic references. The results showed that the success of long-lasting complexion is highly influenced by three main aspects, skin-prep that is adjusted to the skin type, proper layering application techniques, and the selection of compatible products, especially oil-free foundation and silicone primer. Rasiliabrushes uses a systematic approach starting from cleansing, toner and serum application, to final lockdown with setting powder and spray. The layering technique is gradual and precise to create a flawless, long-lasting finish that suits the client's skin needs. In addition to technique, factors such as client comfort, room lighting, and cleanliness of makeup tools also influence makeup success. This study reinforces previous findings that emphasize the importance of personalizing makeup techniques according to skin and environmental conditions. This study contributes to the practice of bridal makeup, and can be used as a reference for MUAs and other researchers in developing long-lasting and effective complexion techniques.